Identification and Analysis of Total Bacteria in the Seagrass Ecosystem of Deep Ambon Bay - Sirajuddin, Nur Tasmiah; Mamesah, Juliaeta A. B.; Sahalessy, Arielno; Simanjuntak, Sania (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
This study aims to identify and analyze the total bacterial count in the seagrass ecosystem of Inner Ambon Bay as part of the microbiological conditions related to anthropogenic activities and pollution levels. It also seeks to determine bacterial species associated with ecological functions in the seagrass ecosystem, thereby providing additional scientific information as a basis for aquatic ecosystem management. Water samples were collected from four different locations, namely Galala Beach, Poka Beach, Tanjung Tiram Beach, and Halong Beach. Physicochemical parameters were measured prior to sampling, and the samples were subsequently analyzed and identified in the laboratory. The results showed variation in total bacterial counts across locations, with the highest value recorded at Galala Beach and the lowest at Halong Beach. Bacterial identification revealed the presence of ten species: Klebsiella aerogenes, Klebsiella pneumoniae, Enterobacter cloacae complex, Enterobacter aerogenes, Serratia odorifera, Citrobacter sp., Pseudomonas aeruginosa, Serratia marcescens, Escherichia coli, and Staphylococcus sp.